Estudio sobre conflictos de competencia entre la jurisdicción especial indígena y la jurisdicción ordinaria a la luz de la jurisprudencia y la doctrina (2010)
The special indigenous jurisdiction empowers indigenous authorities to administer justice in all branches of law according to the usages, customs, rules, and procedures that each indigenous community owns. The main objective of this research is to analyze the conflict of jurisdiction between the indigenous special jurisdiction and general jurisdiction, taking into account case law and national law. The secondary objectives are: to know the limits that a special indigenous jurisdiction has; disseminate that knowledge to all levels of society; and identify the interest that prevails between the special indigenous jurisdiction and the national jurisdiction to present the conflicts of jurisdiction between them. In this investigation we used the descriptive qualitative method. To determine which indigenous jurisdiction is appropriate requires the provision of traditional authority with a vocation to exercise it; that the accused is an active member of an indigenous community; and behaves according to their customs and ancestral customs. The Judge must assess the degree of acculturation of the Indian accused of wrongdoing, to decide whether to apply the special indigenous jurisdiction and to be judged by his own judicial authorities.